A Review of the Nonsurgical Treatment of Oral Leukoplakia. (23rd February 2010) - Ribeiro, Adriana Spinola; Salles, Patrícia Ribeiro; da Silva, Tarcília Aparecida; Mesquita, Ricardo Alves
Abstract : The aim of this paper was to assess the nonsurgical treatment of oral leukoplakia (OL). A medline search from 1983 to 2009 was conducted. The topical or systemic nonsurgical treatments or combination of both was reviewed. The primary outcomes of interest were clinical resolution, malignant transformation, follow-up, and recurrence of OL. Studies showed a rate higher than 50% of clinical resolution with photodynamic therapy, beta-carotene, lycopene, or vitamin A. Few studies reported rates of recurrence from 5 to 67% and of malignant transformation from 8 to 23%. There is a lack of randomized clinical trials that assess the effectiveness of nonsurgical treatment of OL. At this time, randomized controlled trials for nonsurgical treatment of OL demonstrate no evidence of effective treatment in preventing malignant transformation and recurrence. It reinforces that even after clinical resolution, OL should be regularly followed.